Extending the Impact of RAC1b Overexpression to Follicular Thyroid Carcinomas - Márcia Faria; Liliana Capinha; Joana Simões-Pereira; Maria João Bugalho; Ana Luísa Silva (International Journal of Endocrinology)
RAC1b is a hyperactive variant of the small GTPase RAC1 known to be a relevant molecular player in different cancers. Previous studies from our group lead to the evidence that its overexpression in papillary thyroid carcinoma (PTC) is associated with an unfavorable prognosis. In the present study, we intended to extend the analysis of RAC1b expression to thyroid follicular neoplasms and to seek for clinical correlations. RAC1b expression levels were determined by RT-qPCR in thyroid follicular tumor samples comprising 23 follicular thyroid carcinomas (FTCs) and 33 follicular thyroid adenomas (FTAs). RAC1b was found to be overexpressed in 33% of carcinomas while no RAC1b overexpression was documented among follicular adenomas. Patients with a diagnosis of FTC were divided into two groups based on longitudinal evolution and final outcome. RAC1b overexpression was significantly associated with both the presence of distant metastases (P = 0.01) and poorer clinical outcome (P = 0.01) suggesting that, similarly to that previously found in PTCs, RAC1b overexpression in FTCs is also associated with worse outcomes. Furthermore, the absence of RAC1b overexpression in follicular adenomas hints its potential as a molecular marker likely to contribute, in conjunction with other putative markers, to the preoperative differential diagnosis of thyroid follicular lesions.